Onset of Action of Selected Second-Generation Antipsychotics (Pines)–A Systematic Review and Meta-Analyses - Rikke Meyer; Kenneth Skov; Inderjeet Kaur Dhillon; Emilie Olsson; Niels Albert Graudal; Lone Baandrup; Gesche Jürgens (Biomedicines, 2022)
Recommendations for duration of treatment with antipsychotics before considering a switch vary from 2 to 8 weeks, although several studies suggest a rapid onset of action. The objective of this review was to estimate time to onset of action and time to maximum antipsychotic effect of asenapine, olanzapine, quetiapine, and zotepine (pines). We searched bibliographic databases for randomized, placebo-controlled trials in adults with schizophrenia estimating the antipsychotic effect of pines over time. Thirty-five studies including 6331 patients diagnosed with chronic schizophrenia were included. We estimated the standardized mean differences (SMD) of changes in symptom score from baseline to follow-up between intervention and placebo groups across studies using meta-analysis techniques. The summarized effect across all included pines administered as immediate-release formulations showed a statistically significant effect at week 1 (SMD, −0.20 [CI95% −0.28, −0.13]), which increased until week 3 (SMD, −0.42 [CI95% −0.50, −0.34]), after which the effect leveled off (week 6: SMD, −0.53 [CI95% −0.62, −0.44]). The sensitivity analyses of the individual pines confirm this finding, although data sparsity increases variability and limits conclusiveness of these analyses.